Right Aortic Arch and Aberrant Left Subclavian Artery Presenting with Dysphagia Lusoria: A Case Report and Review of the Literature - J. Arudchelvam; M. N. Jazeel (Sri Lanka Journal of Medicine)
Right aortic arch (RAA) occurs in 0.05% to 0.1% of the individuals. Dysphagia lusoria is the difficulty in swallowing due to the compression of the oesophagus due to aberrant vessels. We report a case of aberrant left subclavian artery (ALSA) arising from the RAA resulting in dysphagia in a 59-year-old male. However, he was able to take meals with minimal difficulties. A computerised tomographic scan (CT) of the chest revealed a RAA and an ALSA running posterior to the oesophagus compressing it. Considering that the patient can take meals and maintain his weight, he was managed conservatively.